Change in anterior and posterior curvature after cataract surgery - Kim, Yang Jae; Knorz, Michael C.; Auffarth, Gerd U.; Choi, Chul Y. (Journal of refractive surgery, 2016)
Journal of Refractive Surgery | PURPOSE:To analyze the change in anterior and posterior corneal curvature after cataract surgery using a Placido-dual rotating Scheimpflug device.METHODS:In a prospective cross-sectional study, corneal curvature was measured using the Galilei G4 device (Ziemer Ophthalmic Systems, Port, Switzerland) preoperatively and 1 week and 1, 3, and 6 months after cataract surgery with a temporal limbal
Gesehen am 29.05.2019